2021
DOI: 10.1039/d1ob00710f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, biological evaluation and molecular modeling of urea-containing MraY inhibitors

Abstract: The straightforward synthesis of aminoribosyl uridines substituted by a 5’-methylene-urea is described. Their convergent synthesis involves the urea formation from various activated amides and an azidoribosyl uridine substituted at the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Hits bind to hotspots (HSs) of MraY that were identified by Chung et al [ 31 ] by following two modes (one in 5CKR and one in 6OYH), as previously observed for the urea 13 [ 32 ].…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…Hits bind to hotspots (HSs) of MraY that were identified by Chung et al [ 31 ] by following two modes (one in 5CKR and one in 6OYH), as previously observed for the urea 13 [ 32 ].…”
Section: Resultsmentioning
confidence: 69%
“…The inhibitory activity of the synthesized compounds 2 , ( S , S )- 3a , ( R , R )- 3b , 4 and 5 was evaluated on MraY transferase purified from Aquifex aeolicu s (MraY AA ), which was prepared as previously described by Chung et al [ 39 ]. Their activity was compared to the inhibitory activity of the unprotected amino precursor 12 , urea-containing inhibitor 13 and C - and N -triazole-containing inhibitors 14 and 15 ( Figure 4 ) that we previously synthesized [ 29 , 32 ] ( Table 1 ). Commercially available tunicamycin from Streptomyces sp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations